2022
DOI: 10.1088/1361-6560/aca068
|View full text |Cite
|
Sign up to set email alerts
|

Modeling families of particle distributions with conditional GAN for Monte Carlo SPECT simulations

Abstract: Objective. We propose a method to model families of distributions of particles exiting a phantom with a conditional Generative Adversarial Network (condGAN) during Monte Carlo simulation of SPECT imaging devices. Approach. The proposed condGAN is trained on a low statistics dataset containing the energy, the time, the position and the direction of exiting particles. In addition, it also contains a vector of conditions composed of four dimensions: the initial energy and the position of emitted particles within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Proofs of concept have been published but there are still a lot of unknowns and uncertainties in those approaches that remain to be studied. There is, in particular, some ongoing work on conditional GANs that may allow to model a family of GANs, and to avoid time-consuming re-training (Saporta et al 2022).…”
Section: Artificial Intelligencementioning
confidence: 99%
“…Proofs of concept have been published but there are still a lot of unknowns and uncertainties in those approaches that remain to be studied. There is, in particular, some ongoing work on conditional GANs that may allow to model a family of GANs, and to avoid time-consuming re-training (Saporta et al 2022).…”
Section: Artificial Intelligencementioning
confidence: 99%
“…In previous works (Sarrut et al 2019, 2021a, Saporta et al 2022, it has been shown that Generative Adversarial Network (GAN) can model phase-spaces such that the trained generator neural network approximates a distribution of particles, thereby being able to be used as a fast virtual source model (VSM,e ) of particles. This approach was applied for modeling photon beams from Linac head in radiation therapy treatment (Sarrut et al 2019) and for gammas exiting phantoms or patient Computerized Tomography (CT) during simulation of Single Photon Emission Computerized Tomography (SPECT) systems (Sarrut et al 2021a, Saporta et al 2022. Compared to conventional phase-space files, GAN generators are compact, a few MB instead of a few GB, and can generate particles at high speed (around 10 6 particles per second).…”
Section: Introductionmentioning
confidence: 99%
“…In previous works [1][2][3], it has been shown that Generative Adversarial Network (GAN) can model phase-spaces such that the trained generator neural network approximates a distribution of particles, thereby being able to be used as a fast virtual source model (VSM,e ) of particles. This approach was applied for modeling photon beams from Linac head in radiation therapy treatment [1] and for gammas exiting phantoms or patient CT during simulation of SPECT systems [2; 3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation